2008
DOI: 10.1007/s00122-008-0826-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel tan spot resistance loci beyond the known host-selective toxin insensitivity genes in wheat

Abstract: Tan spot, caused by Pyrenophora tritici-repentis, is a destructive foliar disease of wheat causing significant yield reduction in major wheat growing areas throughout the world. The objective of this study was to identify quantitative trait loci (QTL) conferring resistance to tan spot in the synthetic hexaploid wheat (SHW) line TA4152-60. A doubled haploid (DH) mapping population derived from TA4152-60 x ND495 was inoculated with conidia produced by isolates of each of four virulent races of P. tritici-repenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 47 publications
9
54
1
2
Order By: Relevance
“…Based on the approximate chromosomal positions of individual QTL, a number of genomic regions identified in our studies, including chromosomal arms 3BL, 3DS, 4AL, 5DL, and 7DL, could be the same as reported by Kollers et al (2014), who used 358 European winter wheat accessions. These regions may also correspond to major resistance QTL previously identified in segregating biparental populations (Chu et al 2008b, Faris andSingh et al 2008;Tadesse et al 2007). Gurung et al (2011) identified genomic regions on chromosomes 1D, 2A, 2B, 2D, 4A, and 7D for Pti2 and genomic regions on chromosomes 2D, 6A, and 7D for race 5 in a worldwide spring wheat core collection.…”
Section: Discussionmentioning
confidence: 63%
“…Based on the approximate chromosomal positions of individual QTL, a number of genomic regions identified in our studies, including chromosomal arms 3BL, 3DS, 4AL, 5DL, and 7DL, could be the same as reported by Kollers et al (2014), who used 358 European winter wheat accessions. These regions may also correspond to major resistance QTL previously identified in segregating biparental populations (Chu et al 2008b, Faris andSingh et al 2008;Tadesse et al 2007). Gurung et al (2011) identified genomic regions on chromosomes 1D, 2A, 2B, 2D, 4A, and 7D for Pti2 and genomic regions on chromosomes 2D, 6A, and 7D for race 5 in a worldwide spring wheat core collection.…”
Section: Discussionmentioning
confidence: 63%
“…The toxin insensitivity genes previously identified (Anderson et al 1999;Effertz et al 2002) likely underlines these QTLs (Singh et al 2008a). However, Chu et al (2008) identified five genomic regions significantly associated with tan spot resistance. Three of these novel QTLs located on chromosome arms 2AS, 5AL, and 5BL, conferred resistance to multiple races while the fourth QTL specific to race 3 was observed on chromosome arm 4AL.…”
Section: Quantitative Inheritancementioning
confidence: 96%
“…Additional QTLs have been identified and located on chromosome arms 1AL (Effertz et al 2001), 2AS (Friesen and Faris 2004;Chu et al 2008), 3AS (Singh et al 2008b), 4AL (Faris et al 1997;Friesen and Faris 2004;Faris and Friesen 2005;Chu et al 2008), 5AL (Effertz et al 2001;Chu et al 2008), 1BS (Faris and Friesen 2005), 2BL (Friesen and Faris 2004), 3BS (Faris and Friesen 2005), 3BL (Faris and Friesen 2005), 5BL (Faris and Friesen 2005;Chu et al 2008), 2DS (Faris and Friesen 2005), 2DL (Faris et al 1997), and 7DS (Effertz et al 2001;Faris and Friesen 2005).…”
Section: Introductionmentioning
confidence: 96%